An “Evolved” Devotional Book from Late-Eighteenth-Century Mexico - Taylor, William B. (The catholic historical review, 2015)
A well-used devotional book with two names inscribed and the print of a miraculous image of Christ crucified pasted in next to the first page of text is examined for clues to religious life in Mexico City in the late-eighteenth century. The discussion features a counterpoint between “external” baroque spiritual practices and reforms meant to fix attention on the discipline of private, “internal” exercises and atonement for sins that continues to be a source of scholarly debate.